Paciente con embarazo de 13 semanas de gestación mas hiperemesis gravidica - Salazar Toscano, Hilda Lucia (2018)
Hyperemesis gravidarum is a state of constant sickness and vomiting during pregnancy, associated with dehydration, electrolyte and acid-base disorders, malnutrition and weight loss (> 5%). The prevalence of hyperemesis gravidarum is 0.3-2.3% in all pregnancies. With the aim of applying a nursing care plan in the case of a patient with a pregnancy of 13 weeks of gestation plus Hyperemesis Gravidarum who had lost weight and dehydration. The conceptual framework used was the supplementary and complementary theory of Virginia Henderson. The interventions were based on improving the status of the pregnant woman and avoiding fetal complications, through the application of taxonomies: Nursing Diagnoses (NANDA), Classification of Nursing Outcomes (NOC) and Classification of Nursing Interventions (NIC). Nursing Care Processes are essential to bring the patient and the product to the end of pregnancy in optimal conditions